Penurunan Konsolidasi Tanah Lempung Kecamatan Sambi Kabupaten Boyolali yang Distabilisasi dengan Limbah Keramik - Qunik Wiqoyah; Sinta Thisya Wulandari; Danang Tri Wijaya (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
Based on the preliminary test results, the original soil of the Sambi Boyolali area is classified as inorganic clay with high plasticity. It has a plasticity index value of 31.93%, therefore stabilization is required so that the soil is able to withstand the load of the structure above it. Stabilization was carried out by mixing the soil with ceramic waste that passed the No. 4 sieve with variations of ceramic waste 2.5%, 5%, 7.5%, and 10% of the weight of the soil sample, which aims to determine changes in physical properties and mechanical properties (consolidation settlement) before and after the soil is stabilized. The results of the physical properties test of the soil after being stabilized with ceramic waste showed a decrease in the value of water content, specific gravity, liquid limit value, and plasticity index as well as an increase in the plastic limit value, shrinkage limit value and the amount of soil that passed sieve No. 200. Soil classification changed from inorganic clay with high plasticity in the original soil, to inorganic clay with low plasticity when mixed with 10% ceramic waste. The results of the mechanical test showed an increase in the value of the maximum dry volume weight of the soil (γdmax) as well as the value of the consolidation coefficient (Cv), and a decrease in the compression index value (Cc) and the consolidation settlement value (Sc).